Gender and climate change as new development tropes of vulnerability for the Global South: essentializing gender discourses in Maasailand, Tanzania - Sara de Wit (Tapuya, 2021)
This article explores how international discourses on gender and climate change currently unfold for the Global South, and compares this with earlier gender discourses that traveled to Maasailand (Tanzania). By tracing the genealogy of older gender imaginaries, striking similarities emerge between the traveling discourses which position (African) women as vulnerable. This article argues against the feminization of climate change: the simplistic and historical reproduction of vulnerability along gender binaries. Gender and climate change discourses repeat historical productions of vulnerability and development that lead to a tendency to speak for rather than listen to the very women the discourses seek to support. I argue that more research is needed to understand what women do to live with climate change and its emergent discourses instead of focusing merely on what “climate change does to women.” Discourses on gender and climate change need critical insight from de- and post-colonial critiques of development and (eco)feminist scholarship that foregrounds gender’s intersectional, productive dimensions and agentive qualities. Essentializing categories like the “feminization of poverty” and women as “victims of culture” should serve as cautionary tales for climate change, which can be used by those in power to obscure more urgent problems, such as increasing land dispossession.